Hide and snake - Baker, Keith, 1953- (San Diego : Harcourt Brace, 1991)
A brightly colored snake challenges readers to a game of hide and seek as he hides among familiar objects.
Elem. School Library Collection.
School Library Journal starred.
School Library Journal.
1.7
K-3
Keywords: Snakes -- Fiction; Picture puzzles; Stories in rhyme; Snakes -- Fiction; Stories in rhyme; Puzzles; Snakes -- Fiction; Picture puzzles; Stories in rhyme